Climate and Atmospheric Dynamics and Predictability - Pytharoulis, Ioannis; Katsafados, Petros (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Earth's weather and climate are complex nonlinear systems of dynamical/thermodynamical processes that are highly variable on all spatiotemporal scales. The analysis and prediction of those processes and their feedbacks with the other systems of the biosphere (land and ocean), from the viewpoints of both atmospheric science and dynamics/thermodynamics, can improve our knowledge and have a great impact on society. The main aim of this Special Issue was to gather observational, theoretical and modeling studies on the dynamics of the atmosphere and the climate system, as well as on their predictability at different spatiotemporal scales.